O Compromisso Nacional Criança Alfabetizada (CNCA) como atual política pública de alfabetização no Brasil: Uma análise a partir do enfoque histórico-crítico - Paula, Andréia (Universidade Federal de São Carlos, 2026)
This dissertation is the result of research on the National Commitment to Literate Children (CNCA), established during the government of Luiz Inácio Lula da Silva by Decree No. 11,556, of June 12, 2023. The objective of this investigation is to analyze the limits and possibilities of this policy through its objectives, goals, organization, theoretical conceptions, and bases for the continuing education of literacy teachers under the assumptions of Historical-Critical Pedagogy. The data were obtained through bibliographic and documentary research and allowed for an understanding of literacy, its contradictions, and the historical movements that have accompanied it in Brazilian schools, especially public schools, over time. Therefore, the study sought to understand the history of the main public literacy policies implemented in Brazil and their political and social intentions, as well as to describe literacy from the most diverse hegemonic and counter-hegemonic theoretical perspectives, among which, prominently, is Historical-Critical Pedagogy. The results indicate that the National Commitment to Literate Children (CNCA) is a revisiting of previously established public literacy policies in the country, such as PROFA - the Literacy Teacher Training Program (MEC, 2000) and PNAIC - the National Pact for Literacy at the Right Age (MEC, 2012). These policies are anchored in constructivist assumptions and focus on the continuing education of literacy teachers, making secondary many other factors that interfere with children's literacy, which does not favor its historical and critical understanding and its recognition as a multi-determined process. Furthermore, as a mark of neoliberal influence on Brazilian education, the emphasis given in the National Commitment to Literate Children to large-scale assessments stands out, the objective of which is to generate indicators to satisfy the interests of international organizations such as the World Bank.
The National Commitment to Literate Children (CNCA) as a current public literacy policy in Brazil: An analysis from a historical-critical perspective.
Keywords: Alfabetização; Compromisso Nacional Criança Alfabetizada; Pedagogia Histórico-Crítica; Psicologia Histórico-Cultural; Literacy; National Commitment to Literate Children; Historical-Critical Pedagogy; Historical-Cultural Psychology; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; 4. Educação de Qualidade